Selection Signatures in the First Exon of Paralogous Receptor Kinase Genes from the Sym2 Region of the Pisum sativum L. Genome - Sulima, Anton S.; Zhukov, Vladimir A.; Afonin, Alexey A.; Zhernakov, Aleksandr I.; Tikhonovich, Igor A.; Lutova, Ludmila A. (Frontiers in Plant Science, 2017)
During the initial step of the symbiosis between legumes (Fabaceae) and nitrogen-fixing bacteria (rhizobia), the bacterial signal molecule known as the Nod factor (nodulation factor) is recognized by plant LysM motif-containing receptor-like kinases (LysM-RLKs). The fifth chromosome of barrel medic (Medicago truncatula Gaertn.) contains a cluster of paralogous LysM-RLK genes, one of which is known to participate in symbiosis. In the syntenic region of the pea (Pisum sativum L.) genome, three genes have been identified: PsK1 and PsSym37, two symbiosis-related LysM-RLK genes with known sequences, and the unsequenced PsSym2 gene which presumably encodes a LysM-RLK and is associated with increased selectivity to certain Nod factors. In this work, we identified a new gene encoding a LysM-RLK, designated as PsLykX, within the Sym2 genomic region. We sequenced the first exons (corresponding to the protein receptor domain) of PsSym37, PsK1, and PsLykX from a large set of pea genotypes of diverse origin. The nucleotide diversity of these fragments was estimated and groups of haplotypes for each gene were revealed. Footprints of selection pressure were detected via comparative analyses of SNP distribution across the first exons of these genes and their homologs MtLYK2, MtLYK3, and MtLYK4 from M. truncatula retrieved from the Medicago Hapmap project. Despite the remarkable similarity among all the studied genes, they exhibited contrasting selection signatures, possibly pointing to diversification of their functions. Signatures of balancing selection were found in LysM1-encoding parts of PsSym37 and PsK1, suggesting that the diversity of these parts may be important for pea LysM-RLKs. The first exons of PsSym37 and PsK1 displayed signatures of purifying selection, as well as MtLYK2 of M. truncatula. Evidence of positive selection affecting primarily LysM domains was found in all three investigated M. truncatula genes, as well as in the pea gene PsLykX. The data suggested that PsLykX is a promising candidate for PsSym2, which has remained elusive for more than 30 years.